MERAJUT “KAMPUNG HARAPAN”: PENDEKATAN BUDAYA DAN PARTISIPATORIS DALAM RESOLUSI KONFLIK LATEN DI KAWASAN TRANSMIGRASI TELUK WONDAMA, PAPUA BARAT - Nurrahmi, Iflah Hayati; Vermanda, Diva; Fasya, Muhammad Ilham; Subarkah, Mohammad Gama; Fachruliansyah, Iman (UI Scholars Hub, 2026)
The Werianggi-Werabur Transmigration Area in Teluk Wondama, West Papua, faces challenges of social integration in the form of latent conflict between Indigenous Papuans (OAP) and transmigrants. This tension is manifested in residential segregation and recurring disputes regarding crop damage caused by livestock (